Influence of the effort-reward imbalance in college students on learning engagement: the mediating role of hope and the moderating role of growth mindset - Zhang, Haixia; Wang, Qiangqiang; Xu, Xinyi; Liu, Shengmin (Frontiers in Psychology, 2025)
ObjectiveThis study aimed to investigate the relationship between effort-reward imbalance and learning engagement among college students, as well as the mediating role of hope and the moderating role of a growth mindset.MethodA total of 665 college students participated in this study. The Effort-Reward Imbalance Scale, Hope Scale, Growth Mindset Scale, and Learning Engagement Scale were used.Results(1) Effort-reward imbalance was significantly correlated with hope, learning engagement, and a growth mindset among college students; (2) effort-reward imbalance negatively predicted learning engagement among college students; (3) hope mediated the relationship between effort-reward imbalance and learning engagement; and (4) a growth mindset moderated the relationship between hope and learning engagement. Specifically, a stronger growth mindset mitigated the adverse effects of low hope on learning engagement among college students.ConclusionEffort-reward imbalance influences learning engagement through the mediating role of hope and the moderating role of growth mindset. This implies that fostering a growth mindset among college students can mitigate the negative effects effort-reward imbalance and low hope on their learning engagement.